Impact of damming on nutrient transport and transformation in river systems: A review - Jia-wen Gan; Xun Wang; Qiu-sheng Yuan; Xiao-lei Xing; Sheng Liu; Cheng-gong Du; Yu-ran Zheng; Yun-xin Liu (Water Science and Engineering)
Large-scale damming has emerged as a prevalent global trend, significantly impacting nutrient transport and transformation, as well as the downstream ecological environment. Nitrogen and phosphorus are fundamental elements of primary productivity in aquatic ecosystems and serve as key limiting factors in reservoir eutrophication. This review focuses on the impact of damming on the transport and transformation of nitrogen and phosphorus, regarding changes in nutrient concentrations, fluxes, and proportions. Spatial changes in nitrogen and phosphorus concentrations primarily occur at the inlet and outlet of reservoirs, while temporal changes often exhibit seasonal patterns. At a global scale, phosphorus is preferentially removed from reservoirs compared to nitrogen. The factors influencing the transport and transformation processes of nitrogen and phosphorus in reservoirs include the physicochemical properties of water bodies and human activities. Additionally, nitrogen dynamics are affected by reservoir age, storage capacity, and water storage regulation modes, whereas phosphorus dynamics are also influenced by hydrodynamic conditions. Finally, this review summarizes the impact of damming on the downstream ecological environment and outlines future research directions, providing theoretical support for the management of river–reservoir ecosystems and promoting the green and sustainable development of hydropower in the context of carbon peaking and carbon neutrality goals.